Entrepreneurship in the 21st century : A training guide on entrepreneurship studies for small and medium-scale enterprise development and management - Udeh, John O. (Enugu, Nigeria: The Catholic Institute for Development, Justice and Peace, 1999)
This book provides a clear insight into small and medium scale enterprises as well as their definition and role in a developing economy. It provides a comprehensive guide on how to start a business from conception to preparation of feasibility reports, sourcing of funds and management process. It is a complete and instruction guide on the practical approach to business success.
Includes bibliographical references and index.
nmn 17/08/16
Loans
Keywords: Entrepreneurship; SME